Breaking Barriers of Male Chauvinism: A Case of Dr. Ngozi Okonjo Iweala - Inyang Etim Bassey; Ruth Amiye (dialektika kontemporer, 2022)
Nigerian society still abounds with antiquated and anti-humanist beliefs that portray women as a weaker group and relegate them to inferior positions without regard to their mental capacity and educational competencies. Evidently, Nigerian women are not only increasingly marginalised from advancing in their career lives, but recent studies have shown that they are also excluded from having a political and economic career, which has significant importance to their economic advancement and sustainability, with the sole notion that the women are incapable of initiating any meaningful development. Although there are no constitutional barriers to women's increased participation in social, political, and economic advancement, there are societal and cultural barriers that stymie women's political and economic advancement. Some of these barriers include, but are not limited to, traditions, religious practice, work-life imbalance, and discriminatory organisational structures, among others. The paper employs both secondary and tertiary sources of data and adopts the historical research method in assembling and interrogating the data sourced for this research. The study argued that despite the general antiquated and anti-humanist belief that women are incapable of initiating any meaningful development in Nigerian society, findings from this study indicate that few Nigerian women have distinguished themselves both nationally and internationally, and one of such individuals is Dr. Ngozi Okonjo Iweala, who has not only broken barriers of male chauvinism in the global landscape but has also redefined the status quo of women.